Pelatihan Pembuatan Donat Menggunakan Tepung Protein Sedang dan Tinggi di Kelurahan Pulo Brayan Darat II Lingkungan X Medan Timur - Laila, Yusra; Dewi, Mila Ariska; Lubis, Retnita Ernayani (Medan Resource Center, 2024)
This study investigates the influence of flour type (Segitiga Biru and Cakra) and yeast ratio (5 grams and 10 grams) on the sensory quality of fermented donuts, using proofing durations of 30 and 60 minutes. An experimental design was employed with eight treatment combinations. The donut-making process included ingredient mixing, proofing, and frying. Organoleptic evaluations were conducted on taste, texture, and aroma, with panelists comprising university students aged 20–30 years. The findings reveal that donuts made with Cakra Flour, 5 grams of yeast, and proofing durations of 30 minutes (C1) and 60 minutes (C2) exhibited the best quality, receiving a preference score of 65. In contrast, donuts using Segitiga Biru Flour with 10 grams of yeast and proofing times of 30 minutes (B3) and 60 minutes (B4) resulted in suboptimal texture and aroma. These results underscore the significance of selecting high-quality raw materials and optimizing fermentation conditions to enhance the sensory attributes of fermented donuts.